Aspek Caring Perawat dalam Perawatan Pasien ARDS COVID-19 Terpasang Extracorporeal Membrane Oxigenation (Ecmo): Studi Kasus dengan Pendekatan Teori Keperawatan Care, Core and Cure Lydia Hall - Yudi Elyas; Sri Yona; Agung Waluyo (Jurnal Keperawatan Silampari, 2022)
This study aims to provide an overview of nurses' caring in carrying out critical nursing care for Covid-19 patients installed with Extracorporeal Membrane Oxygenation (ECMO) in the ICU using the Care, Core, Cure Lydia Hall nursing theory. This type of research is qualitative research with a case study approach. The results showed that nursing problems that occurred in patients after ECMO installation included airway disorders, gas exchange disorders, bleeding risks, and the risk of impaired skin integrity due to decreased tissue perfusion. In conclusion, Lydia Hall's nursing theory is dominated by the Cure aspect because the installation of ECMO is a very complex medical procedure and involves teams from various disciplines. Hence, the implementation of the Cure aspect is a collaborative act of nurses. Care and Core aspects also have an essential role in caring for nurses, namely by conducting therapeutic interactions and facilitating patients to get family support so that patients have the spirit to recover and do not experience stress that can affect hemodynamic conditions. Keywords: COVID-19, ECMO, ICU, Lydia Hall, Case Study